HPV vaccine hesitancy among parents of female adolescents: a pre–post interventional study. (September 2017) - Palmeri, S.; Costantino, C.; D'Angelo, C.; Casuccio, N.; Ventura, G.; Vitale, F.; Pojero, F.; Casuccio, A.
Highlights: Poor communication is a relevant factor of low immunisation coverage. This phenomenon may be bypassed by adequate counselling provided to parents. Role of healthcare workers is fundamental in promotion of human papillomavirus vaccination.